Profiling signaling polarity in chemotactic cells - Wang, Yingchun (National Academy of Sciences, 2007)
Cell movement requires morphological polarization characterized by formation of a leading pseudopodium (PD) at the front and a trailing rear at the back. However, little is known about how protein networks are spatially integrated to regulate this process at the system level. Here, we apply global proteome profiling in combination with newly developed quantitative phosphoproteomics approaches for comparative analysis of the cell body (CB) and PD proteome of chemotactic cells. The spatial relationship of 3,509 proteins and 228 distinct sites of phosphorylation were mapped revealing networks of signaling proteins that partition to the PD and/or the CB compartments. The major network represented in the PD includes integrin signaling, actin regulatory, and axon guidance proteins, whereas the CB consists of DNA/RNA metabolism, cell cycle regulation, and structural maintenance. Our findings provide insight into the spatial organization of signaling networks that control cell movement and provide a comprehensive system-wide profile of proteins and phosphorylation sites that control cell polarization.